Differentiated instruction effectiveness on the secondary stage students’ reading comprehension proficiency level in Jordan - Ibrahim Suleiman Magableh; Amelia Abdullah (International Journal of Evaluation and Research in Education (IJERE), 2022)
Differentiated instruction (DI) is a teaching approach involves several strategies in which teachers adapt, modify, adjust and change instruction to respond to students’ diverse individual needs in heterogeneous classrooms. The study aimed at exploring the effectiveness of DI on secondary stage students’ proficiency level. The study followed the quantitative quasi-experimental design in which data were collected from the pre/post achievement tests administered at the initiation and the completion of the intervention. A total of 80 grade 11 students from both genders participated in the study. A number of (N=40) males and (N=40) females from four public schools in Jordan were distributed into (N=40) for the experimental group and another (N=40) from both genders for the control groups. The experimental group received education using DI strategies of homogeneous groups, tiered assignments and tiered instruction in the areas of content, process, product and learning environment. Conversely, the control groups received education through the one-size-fits-all method. Analysis of covariance (ANCOVA) results showed that DI affected reading comprehension scores positively, and the respondents of the experimental groups outperformed their counterparts of the control group. Moreover, the above-average respondents statistically outperformed the other proficiency levels. However, the findings indicated no statistically significant difference related to gender.